A case of Paget-Schroetter syndrome (PSS) in a young judo tutor: a case report. (December 2016) - Ijaopo, Ruth; Oguntolu, Victor; DCosta, Dominick; Garnham, Andrew; Hobbs, Simon
Abstract Background We present a case of unsuspected Paget-Schroetter syndrome (also calledeffort thrombosis ), one of the rare causes of upper extremity deep vein thrombosis. To the best of our knowledge, this was the first such case in our hospital. Our patient may have been discharged with an incomplete diagnosis and inappropriate management but for one of the few physicians who knew about effort thrombosis, made the diagnosis, and referred the patient promptly to the appropriate team. Case presentation A 37-year-old Caucasian man who was an active judo tutor presented to the acute medical unit in our hospital. He had initially presented to his primary care physician complaining of redness and swelling of his right arm and elbow of 1 week's duration. He had been prescribed some antibiotics by his general practitioner, but his symptoms worsened. At that point, he was referred to our hospital for further review of his arm swelling. Conclusions When considering a diagnosis of deep vein thrombosis, the age, hobbies, and occupation, among other things, of individual patients should be put into context at all times to avoid missing rare causes such as Paget-Schroetter syndrome. This report is intended to raise awareness of this rare condition. Knowledge of this condition and its management is essential for all medical practitioners, especially medical doctors who are involved in unselected medical admissions in accident and emergency or medical admission units, where the majority of such patients are seen.